2002
DOI: 10.1002/ana.10274
|View full text |Cite
|
Sign up to set email alerts
|

Premotor cortex is involved in restoration of gait in stroke

Abstract: Cortical activation during hemiplegic gait was assessed in six nonambulatory patients with severe stroke (four men, two women; four with right and two with left hemiplegia; 57 years old and 3 months after stroke on average), using a near-infrared spectroscopic imaging system. Each patient performed tasks of treadmill walking (0.2km/hr), alternated with rest every 30 seconds for four repetitions, under partial body weight support, either with mechanical assistance in swinging the paretic leg control (CON) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(136 citation statements)
references
References 39 publications
3
131
1
Order By: Relevance
“…In tandem with the PFC, the SMA is an important region in human locomotion and finetuning balance with increased walking speed. In previous literature, spinal locomotor pattern generators have been primarily thought to mediate rhythmic locomotor movement [17][18][19]. However, based on this assumption, we should have observed a decrease in cortical activation associated with increased walking speeds.…”
Section: Discussionmentioning
confidence: 73%
“…In tandem with the PFC, the SMA is an important region in human locomotion and finetuning balance with increased walking speed. In previous literature, spinal locomotor pattern generators have been primarily thought to mediate rhythmic locomotor movement [17][18][19]. However, based on this assumption, we should have observed a decrease in cortical activation associated with increased walking speeds.…”
Section: Discussionmentioning
confidence: 73%
“…Can functional neuroimaging reflect training-related reorganization and provide a physiological insight into the optimal dose of additional gait training? Walking is not feasible during fMRI but has been performed during near-infrared spectroscopy (NIRS) (Miyai et al, 2001(Miyai et al, , 2002, 18 fluorodeoxyglucose PET (Dobkin, 1996), and single photon emission computerized tomography (Fukuyama et al, 1997). Bilateral cortical activity was found in primary and secondary motor cortices and the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…In hemispheric stroke patients with supratentorial lesions, activation in the motor-related cortex in the affected hemisphere increases with functional recovery. Particularly, the premotor cortex in the affected hemisphere appears to be essential (Miyai et al, 2002(Miyai et al, , 2003, as a previous observational study had suggested (Miyai et al, 1999). On the other hand, ataxic stroke patients with infratentorial lesions display a different activation pattern during gait.…”
Section: Cortical Activation Of Gait In Stroke Patientsmentioning
confidence: 78%